THE CHALLENGE FOR INDONESIAN BIOFUEL GOVERNANCE: STUDY CASE OF STATE-BUSINESS RELATION BETWEEN KORINDO AND INDONESIAN GOVERNMENT ON CRUDE PALM OIL BUSINESS - Aji Said Iqbal Muhammad Iqbal Fajri; Darynaufal Mulyaman (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
The Indonesian government has initiated a big-push strategy to make crude palm oil (CPO) the main commodity for its biofuel mandates. However, this strategy has resulted in many environmental and political concerns. One case worth noting is the alleged rainforest burning in Papua by Korea-Indonesia conglomerate company named Korindo at the end of 2020. This case raised public concern over the environmental preserving effort at one of the most extensive natural rainforests globally, which is essential for Indonesia’s biodiversity and climate actions. Moreover, Korindo has also allegedly correlated to human rights abuses, mainly in the form of land-grabbing and the utilization of police force in the plantation area. Using state-business relations as its framework, this paper argues that even Korindo does not comply with sustainability measures, it can still sell its CPO to Indonesia’s biofuel market due to increasing demand from biofuel mandates. Keyword(s): CPO, Biofuel, Korindo, State-Business Relations